Perceived benefit is the strongest determinant factor of medication adherence in the elderly with hypertension - I Gede Putu Darma Suyasa; Ni Made Ari Widayani; Ni Putu Kamaryati; Ni Made Sri Rahyanti (Jurnal Keperawatan Padjadjaran, 2024)
Background: The level of medication adherence among the elderly with hypertension is decreasing globally, including in Indonesia. Medication adherence is a major factor in treatment effectiveness for hypertensive patients. The Health Belief Model is one of the theories illustrating factors influencing patients’ medication adherence. Purpose: This study aimed to analyze determinant factors of medication adherence among the elderly with hypertension based on the application of the health belief model. Methods: This is a descriptive-analytic study with a cross-sectional approach. Sampling used a proportional stratified random sampling technique involving 193 patients with hypertension recruited from one of the Regional General Hospitals in Denpasar City Center. Data were obtained using three questionnaires, namely demographic characteristics, the health belief model (HBM), and the Morisky Medication Adherence Scale (MMAS-8). Data were analyzed using binary logistic regression. Results: The research results showed the majority of respondents (62.7%) were compliant in taking medication. Multivariate test results showed that perceived susceptibility (p <0.001; AOR: 5.163), perceived benefits (p <0.001; AOR: 12.061), self-efficacy (p <0.001; AOR: 3.213), perceived barriers (p <0.001; AOR: 0.133) and cues to action (p <0.001; AOR: 3.480) is related to medication adherence in the elderly with hypertension. Conclusions: Perceived benefit is the strongest determining factor of medication adherence among the elderly with hypertension. Respondents with high belief in perceived benefits tend to adhere to medication 12.061 times compared to respondents with low belief in perceived benefits. Health workers are advised to increase the elderly's belief in the perceived benefits and perceived susceptibility to increase their medication adherence.